Studies of Joshi Effect in Mercury Vapour with a Triode under Various Modes of Detection Mechanism - Prashad, Jagdish (Asian Journal of Chemistry, 2010)
Production of Joshi effect ± Δi in mercury vapour excited by a transformer discharge in the range 0.48 kV to 1.00 kV, 50 Hz has been studied with triode 30 coupled resistively with L.T. line using it as anode bend (α) and grid leak (β) detectors. The observations of iD,L are taken in plate as well as in grid currents. For the observations in grid currents, at a given applied potential, iD and -Δi are in the order β > α at lower values of the resistance R; at its higher values, they are in the order α >β. The corresponding -%Δi is, however, in the order α > β for lower values of R, and in the order β > α for the higher values of R. For the observations in grid current, at a given applied potential, iD is in the order α > β ; the corresponding -Δi and -%Δi are in the order β > α . Remarkably enough no positive effect +Δi has been observed in grid leak detection when the observations are taken in plate current, whereas for higher values of R- for and above 1 megohm, positive effect upto the magnitude of +44% is observed under anode bend detection. For the observations in grid current, grid leak detection gives +11500% Δi at Vm, while in the case of anode bend detection, a slight positive effect only 1 % maximum, is given at 0.92 kV and onwards, and at high values of R. The results have been explained on the basis of Joshi theory for the phenomenon ±Δi..